2016
DOI: 10.1002/micr.30026
|View full text |Cite
|
Sign up to set email alerts
|

Technique and outcomes of laparoscopic bulge repair after abdominal free flap reconstruction

Abstract: Although uncommon, bulge formation after abdominal free flap reconstruction can create significant morbidity to patients. Laproscopic hernia repair using composite mesh underlay offers an alternative to traditional open hernia repair and can be successfully used to minimize scarring, infection, and pain to free flap patients who have already undergone significant reconstructive procedures. © 2016 Wiley Periodicals, Inc. Microsurgery 36:367-371, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…No individual study within this review demonstrated increased risk of abdominal wall morbidity including hernia, bulge, or abdominal wall laxity following free tissue transfer in this cohort (►Table 4). 4,7,15,31,34,36,42,43,45,51 However, in a subgroup analysis, Wes et al found that while patients with prior hernia repair were more likely to develop a bulge following abdominal free tissue transfer, this was not true for their overall abdominal scar cohort. 15 Similarly, Roostaeian et al demonstrated that patients with no prior history of abdominal surgery who underwent MS-0 or MS-1 free flap reconstructions were at higher risk of postoperative bulge compared with patients with prior abdominal surgery, however, this difference did not remain for MS-2 and MS-3 reconstruction types.…”
Section: Postoperative Abdominal Wall Morbiditymentioning
confidence: 99%
“…No individual study within this review demonstrated increased risk of abdominal wall morbidity including hernia, bulge, or abdominal wall laxity following free tissue transfer in this cohort (►Table 4). 4,7,15,31,34,36,42,43,45,51 However, in a subgroup analysis, Wes et al found that while patients with prior hernia repair were more likely to develop a bulge following abdominal free tissue transfer, this was not true for their overall abdominal scar cohort. 15 Similarly, Roostaeian et al demonstrated that patients with no prior history of abdominal surgery who underwent MS-0 or MS-1 free flap reconstructions were at higher risk of postoperative bulge compared with patients with prior abdominal surgery, however, this difference did not remain for MS-2 and MS-3 reconstruction types.…”
Section: Postoperative Abdominal Wall Morbiditymentioning
confidence: 99%